Towards a post-naturalist architecture: a systematic review of nature-culture relationship in ecological architecture - Zafer Küçük, Seda; Ciravoğlu, Ayşen (Estoa. Journal of the Faculty of Architecture and Urbanism, 2026)
Studies on nature-culture relations emphasize the intertwined cultural relationship between the natural world and human culture. In recent years, there has been an increase in practices that include non-human entities, expanding the scope of architectural design. This review explores current approaches that examine the relationship between nature and culture in the context of ecology in architectural design. The data were collected from the Scopus and Web of Science databases guided by PRISMA The Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Information regarding the post-naturalist perspective in architecture was derived from an analysis of contemporary studies that address the nature-culture discourse and expand the relationship between ecological principles and architectural design. The findings demonstrate that the domain of architectural design can be expanded through the incorporation of alternatives that are frequently perceived as threatening, overlooked, marginalized, or defective, particularly in relation to ecological considerations. This review promotes alternative ecological practices by highlighting innovative architectural design concepts and strategies.